Analisis Fiqh Siyasah Terhadap Putusan Mk Nomor 23/Puu-Xviii/2020 (Judicial Review Perppu Nomor 1 Tahun 2020 ) - Mardiah, Rayhan (Hukum tata Negara/Siyasah, 2024)
ABSTRACTThe Constitutional Court (MK) in Indonesia cannot be separated from the historical exploration of the concept and facts regarding judicial review, which is the most important authority of the Constitutional Court. Judicial review or the right to material review is the process of testing lower laws and regulations against higher laws and regulations carried out by judicial institutions. The formulation of the problem in this study is about how the Constitutional Court judges consider making decisions on decision No. 23/PUU-XVIII/2020 (Judicial Review of Perppu No. 1 of 2020 concerning State Financial Policy and Financial System Stability for the Handling of the Corona Virus Disease 19 (Covid-19) Pandemic and/or in the Context of Facing Threats that Endanger the National Economy and/or Financial System Stability) as well as a study of fiqh siyasah on the decision. This research method uses a normative and descriptive method. The conclusion of this study is that the Judicial Review submitted by, Amien Rais, Din Syamsuddin, Sri Edi Swasono on April 14, 2020 and on the official website of the Constitutional Court, the material test of Perppu No. 1 of 2020 has been accepted by the Constitutional Court with receipt number 1962/PAN.MK/IV/2020 but the Constitutional Court led by Judge Anwar Usman decided not to accept the submission of Judicial Review with the consideration that Perppu No. 1 of 2020 has officially become Law No. 2 of 2020 so that the application has lost its legal object. The study of fiqh siyasah in this study is included in the discussion of Siyasah Dusturiyyah.Keywords: Judicial Review, Constitutional Court. ABSTRAKMahkamah Konstitusi (MK) di Indonesia tidak dapat lepas dari jelajah historis konsep dan fakta mengenai judicial review, yang merupakan kewenangan paling utama lembaga MK. Judicial review atau hak uji materi merupakan proses pengujian peraturan perundang-undangan yang lebih rendah terhadap peraturan perundang-undangan lebih tinggi yang dilakukan oleh lembaga peradilan. Adapun rumusan masalah dalam penelitian in tentang Bagaimana pertimbangan hakim MK dalam mengambil keputusan terhadap putusan Nomor 23/PUU-XVIII/2020 (Judicial Review Perppu Nomor 1 Tahun 2020 Tentang Kebijakan Keuangan Negara Dan Stabilitas Sistem Keuangan Untuk Penanganan Pandemi Corona Virus Disease 19 (Covid-19) Dan/Atau Dalam Rangka Menghadapi Ancaman Yang Membahayakan Perekonomian Nasional Dan/Atau Stabilitas Sistem Keuangan) serta kajian kajian fiqh siyasah terhadap putusan tersebut. Metode penelitian ini menggunakan metode normative serta bersifat deskriptif. Kesimpulan dari penelitian ini adalah bahwa Judicial Review yang diajukan oleh , Amien Rais, Din Syamsuddin, Sri Edi Swasono pada tanggal 14 April 2020 dan dalam laman resmi MK, uji materi Perppu No. 1 Tahun 2020 telah diterima MK dengan nomor tanda terima 1962/PAN.MK/IV/2020 namun MK yang dipimpin oleh Hakim Anwar Usman memutuskan untuk tidak menerima pengajuan Judicial Review dengan pertimbangan bahwa Perppu No. 1 Tahun 2020 telah resmi menjadi Undang-undang No. 2 Tahun 2020 sehingga permohonan tersebut telah kehilangan objek hukumnya. Kajian fiqh siyasah dalam penelitian ini masuk dalam pembahasan Siyasah Dusturiyyah.Kata Kunci: Judicial Review, Mahkamah Konstitusi.